Early-Onset Sepsis in Neonates - A Population-Based Study in South-West Norway From 1996 to 2018 - Vatne, Anlaug; Klingenberg, Claus; Rettedal, Siren; Øymar, Knut (Frontiers in Pediatrics, 2021)
Background The epidemiology of early-onset sepsis (EOS) may change over time. Longitudinal surveillance of causative pathogens, antibiotic susceptibility patterns and antibiotic therapy is important for optimal therapy strategies. Objectives To describe the incidence of EOS, causative pathogens, antibiotic susceptibility patterns and antibiotic therapy over a 23-year period. Methods Retrospective population-based study from a single-center neonatal intensive care unit at Stavanger University Hospital, Norway, covering a population in South-West Norway, during the 23-year period 1996-2018. Results Of 104 377 live born infants, 101 infants (0.97/1000) had culture-confirmed EOS; 89 with Gram positive and 12 with Gram-negative bacteria. The EOS-attributable mortality was 6/101 (5.8%). For the three most prevalent pathogens the incidences were; Group B streptococcus (GBS) 0.57/1000, Escherichia coli 0.11/1000 and viridans group streptococci (VGS) 0.10/1000. GBS was the most common pathogen (59/93; 63%) in infants with gestational age (GA) ≥ 28 weeks. In contrast, among extremely preterm infants (GA <28 weeks) the incidence of E. coli infection was higher than for GBS infection. The second most common bacterial pathogens causing EOS among term infants were VGS. There was no change in the incidence of EOS for the entire study period, but from 2000 to 2018 there was a mean decline in EOS by 6% per year (95% CI 1%-10%) (p=0.019). The incidences of GBS and E. coli did not change during the study period. The initial empirical antibiotic regimen for EOS was in all cases a combination of benzylpenicillin or ampicillin and an aminoglycoside, but in 21/101 (21%) of cases a broad-spectrum antibiotic was either added or substituted this regimen. In 2/101 (2%) EOS cases, the pathogens were nonsusceptible to the empirical antibiotic regimen. All E. coli isolates were susceptible to aminoglycosides. Conclusion Gram-positive bacteria were the most common causative pathogens in EOS, but Gram-negative bacteria dominated in infants with GA <28 weeks. There was no change in the incidence of EOS during the entire study period. The current empiric regimen with benzylpenicillin and gentamicin provides a very high coverage for EOS in our setting.